Intellectual property law for engineers, scientists, and entrepreneurs / Howard B Rockman - Rockman, Howard B.
This book informs engineering and science students, technology professionals, and entrepreneurs about the intellectual property laws that are important in their careers. It covers all of the major areas of intellectual property development and protection in non-legalistic terms that are understandable to technology and science professionals. New material includes a comprehensive discussion on the American Invents Act (AIA), coverage of many new high-profile topics, such as patent protection the mobile communications industry, and a new chapter on "The Future of Technology, Engineering, and Intellectual Property."